SISTEM PENGAMBILAN KEPUTUSAN PEMETAAN PELATIHAN TEKNOLOGI INFORMASI UNTUK PENYANDANG DISABILITAS TUNA RUNGU HARD OF HEARING MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Siti Ummi Masruroh; Ahmad Arya Swaraja; Imam Marzuki Shofi (JURNAL TEKNIK INFORMATIKA, 2019)
Law number 8 of 2016 states that disability is part of the Indonesian republic which has the same rights and obligations. Therefore the need to increase social welfare for persons with disabilities, one way to improve it is by providing information technology training. To support information technology training an appropriate training mapping is needed. In this study, a training mapping was carried out for persons with disabilities who were deaf where there was ranking at each information technology training based on the ability criteria. The ranking of information technology training is analyzed using the Analytical Hierarchy Process (AHP) method and for the system, development using Rapid Application Development (RAD). This research discusses the hard of hearing deafness disability, in which information technology training is used like the following attributes of Microsoft Word, Microsoft Excel, PowerPoint, Photoshop, Scratch Programming, Adobe illustration, e-marketing, internet browsing, and social media. The final results show the ranking of information technology training that is suitable for hearing deafness disability.